Building a small hybrid air-ground vehicle - Wongso, Edward Steven (Nanyang Technological University, 2024)
This final year project focuses on building a lightweight hybrid air-ground robot. The prototype consists of a bicopter on top and a balance bot on the bottom. The hybrid configuration takes the best thing out of both worlds, active wheels on the ground with great efficiency and brushless motor with propeller with the maneuverability in the air. The hybrid configuration allows the prototype to move on the ground using very little power consumption and fly in the air to reach difficult environments, making the prototype versatile and efficient. The prototype also boasts a complex control system where switching between driving modes are seamless. The target of the prototype is for future researchers to implement different control algorithms in this type of configuration in a safer and hassle-free manner.